Isolation and partial characterization of organophosphate pesticide degrading bacteria from soil sample of Noakhali, Bangladesh - Reza, Mahin; Fiza, Jannatul; Hossen, Foysal; Ahmed, Firoz (Bangladesh Journal of Microbiology, 2019)
Extensive use of organophosphate pesticides particularly malathion can result in pollution of soil, surface water and ground water, and thus disrupts ecosystem byexposing non-target species to its toxicity. Bioremediation with indigenous microorganisms having pesticide utilizing abilities is considered to be a viable solution regarding decontamination of organophosphate residues from pesticide contaminated soil. In this study, we isolated five malathion degrading bacter ial strains designated as S-1, S-2, S-3, S-4 and S-5 from paddy fields of Noakhali, Bangladesh by observing visible growth in malathion supplemented mineral salts medium (MSM) agar following selective enrichment technique. The isolates were provisionally identified based on their morphological and biochemical characteristics as Pseudomonas spp. (S-1), Bacillus subtilis (S-2), Staphylococcus aureus (S-3), Pseudomonas aeruginosa (S-4) and Pseudomonas spp. (S-5) respectively. To determine their malathion utilization potential, the isolates were inoculated in MSM containing 50 mg/l malathion as sole source of carbon. When compared with control, the turbidometric growth study with the isolates revealed that all the isolates showed a significant increase of growth, indicating utilization of malathion (conc. 50 mg/l) in MSM at 37oC. The rate of growth varied for all the isolates when this growth study was done using different temperature schemes (25oC, 35oC and 45oC). Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 17-22